TYPES OF BIOSORBENTS OBTAINED BY CHEMICAL MODIFICATION OF WASTE FROM FOOD PRODUCTION ENTERPRISES (Multidisciplinary Journal of Science and Technology, 2024)
Biomasses of microorganisms are used as sorbents in the determination and sorption separation of heavy metal ions from the composition of industrial effluents and waste. A biosorbent was prepared from Saccharomyces Cerevisiae microorganism and yogurt whey, and the composition of the biomasses was studied.